MANAJEMEN LAYANAN SIRKULASI PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH PONTIANAK - Hartini, Ela; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThe purpose of this study was to know the management of library circulation services in the library University of Muhammadiyah Pontianak. This research was descriptive research and research method used was qualitative method. Data collection technique used by researcher in this research were observation, interview, and documentation. Theory used in this research was According to George R. Terry, management functions for the operative level of management can be limited and formulated: (1) planning, (2) organizing, (3) actuating, and (4) controlling. The Informants in this study were two (2) persons who are selected based on criteria that have been set. The result of the research is the form of management of circulation service that has been developed with automation system to facilitate the activity on the circulation service. In the process of implementation of automated circulation activities, there are some obstacles and non-conformity in the implementation undertaken. That was as experienced in the Muhammadiyah University Library Pontianak who experience interruption in the circulation services because the server owned by the library has interference. Keywords: library management, circulation services, excellent service